Leaf Production Responses of Lampeni (Ardisia humilis Vahl.) to Types and Rates of Manure Application - Aziz, Sandra Arifin; Wardani, Eska Ayu (Journal of Tropical Crop Science, 2019)
Ardisia humilis (Myrsinaceae), known as Lampeni (in Indonesia), is part of the wild flora in Southeast Asia and is known as a weed in some countries. The leaf has medicinal properties for some diseases. The leaves and fruit of this plant are believed to be a treatment for tuberculosis, lung disease, hepatitis, chronic bronchitis, and menstrual irregularities in women. Research into the cultivation of Lampeni is needed to support its usage in Indonesia. The objectives of the research reported here were to find the types and rates of manure to promote leaf production. An experiment was carried out at IPB Experimental Station, Cikarawang Dramaga, Bogor, Indonesia, from December to June 2016. The experiment was laid out in a split plot design with manure types (chicken and cow manure) as main plots and application rates (0, 5, 10, and 15 t ha-1) as sub-plots. The results of the experiment showed that vegetative growth increased with manure application. Total branch number, LAI, leaf fresh and dry weight were higher with 15 t.ha-1 chicken manure or 5 t.ha-1 cow manure application. Leaf analysis showed that pigment concentration responded negatively to increasing manure application and the highest pigment concentration was found on the plants without manure application.